2015
DOI: 10.1093/jac/dkv107
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MDR and XDR Streptococcus pneumoniae in Canada, 2007–13

Abstract: Though the rate of MDR S. pneumoniae has remained relatively stable since 2007, XDR strains have emerged in Canada. These strains are virulent, possess resistance determinants and are related to international clones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 17 publications
2
35
0
2
Order By: Relevance
“…Besides vaccine use, clonal success of CC320 and other serotype 19A clones is attributed to antibiotic selective pressure [17]. Indeed, in the present study we observed that all CC320 isolates had an MDR phenotype with high β-lactam MICs, which is in agreement with previous studies [6,13,22]. However, in European Russia, CC320 has replaced another highly resistant clone, CC663.…”
Section: Discussionsupporting
confidence: 92%
“…Besides vaccine use, clonal success of CC320 and other serotype 19A clones is attributed to antibiotic selective pressure [17]. Indeed, in the present study we observed that all CC320 isolates had an MDR phenotype with high β-lactam MICs, which is in agreement with previous studies [6,13,22]. However, in European Russia, CC320 has replaced another highly resistant clone, CC663.…”
Section: Discussionsupporting
confidence: 92%
“…Analysis of lefamulin results by infection type and by geographic region showed no a MDR and XDR status was based on nonsusceptibility to Ն3 and Ն5 classes, respectively, of the following antimicrobial agents, as described by Golden et al (30) and applying the following breakpoints: penicillin (MIC, Ն4 g/ml), ceftriaxone (MIC, Ն2 g/ml), erythromycin (MIC, Ն0.5 g/ml), clindamycin (MIC, Ն0.5 g/ml), levofloxacin (MIC, Ն4 g/ml), tetracycline (MIC, Ն2 g/ml), and trimethoprim-sulfamethoxazole (MIC, Ն1 g/ml). MDR, multidrug resistant; XDR, extensive drug resistant.…”
mentioning
confidence: 99%
“…Broth microdilution test was used to measure the minimum inhibitory concentration (MIC) within a limited concentration range of ten antimicrobial agents (penicillin [ 33,34 For an isolate (SRP2368) that demonstrated resistance to LVX (MIC ‡8 mg/mL), susceptibility to fluoroquinolones (FQs) (LVX and ciprofloxacin [CIP]) was further analyzed by the standard broth microdilution method, and mutations in the quinolone resistance-determining regions (QRDRs) of DNA gyrase genes (gyrA and gyrB) and topoisomerase IV genes ( parC and parE) were analyzed as described previously. 35 Full-length nucleotide sequences of gyrA and parC genes were determined with PCR and direct sequencing.…”
Section: Antimicrobial Susceptibility Testing and Genetic Analysis Ofmentioning
confidence: 99%